INDONESIA-MALAYSIA’S LEGAL PROTECTION FOR BUSINESSES UNDER THE COD (CASH ON DELIVERY) PAYMENT SCHEME IN THE MARKETPLACE - Sugirman, Andi; Waruwu, Monaldus Fatiso; A, Abdussalam; Ardiana, Ulfa (Institut Agama Islam Negeri Bone, 2024)
ABSTRACTThe COD (Cash on Delivery) can impact cash flow due to payment delays, especially for businesses with tight margins. In order to address the issue of business actors' legal protection when using COD as a payment mechanism in the marketplace, this paper seeks a solution. Research on laws and other relevant legal literature is done by the author as part of the normative juridical legal research approach used to write this publication. To make corporate operations more productive and efficient, Marketplace aims to reduce their unnecessary complexity. With the marketplace emerging, everyone may now purchase and sell goods and services with ease, at a low cost, and in a timely manner, as there are no restrictions on location, time, or distance. Â There are numerous payment methods available in the marketplace, one of which is COD (Cash on Delivery), which allows customers to pay directly on the spot when they receive the things they ordered. However, in practice, the parties who transact in the Marketplace frequently suffer significant losses, necessitating the existence of legal protection for the parties that transact in the Marketplace, both consumers and business entities, in order to protect their rights.